Gender specific honor codes and cultural change. (May 2013) - Cihangir, Sezgin
The current research investigates two main goals. First, it investigates the cultural and gender differences in gender specific honor codes among youth ( N =482) from cultures with a high orientation on honor (Moroccan vs. Turkish) compared to youth from a culture with a low orientation on honor (native Dutch). Second, the current research investigates the cultural change in values underlying honor codes. Before an educational program, a pre-training test assessed the perceived determinants (i.e., religion, culture, parents and other close relatives, and friends and peers) of honor. Furthermore, the perceived importance of sexual purity of female and male family members for honor, and the perceived responsibility for the sexual purity of female family members were assessed. In addition, the current study also investigated whether students from cultures with a high orientation on honor vs. cultures with a low orientation on honor are able to indicate different types of violence as honor related, and to what extent they endorse violence against themselves when they would violate their family honor. The results of the current study shows that cultural change in cultural beliefs and attitudes underlying honor is possible through educational programs. The implications of the findings are discussed.